Analisis Sewa-Menyewa Dalam Skema Outsourcing Undang-Undang Nomor 13 Tahun 2003 - Muhammad Isa; Muhammad Azzam Alghifary (INSTITUT AGAMA ISLAM TAZKIA, 2020)
Outsourcing categorized as employee service leasing schema based on Law ofThe Law Number 13 of 2003 about employment. Islam is a religion that organize all muamalahaspect as outsourcing as well which known as ijarah.This research is provided as descriptive using qualititative comparison. To compareoutsourcing contract mechanism with ijarah contract mechanism. According legal law, Law ofThe Law Number 13 of 2003 and Islamic Econormic Law.Analysis of this two comparison resulting that outsouring contract mechanism is Nomortcontradiction with ijarah contract. Basically, the principes and the requirement of ijarah contractis on outsourcing.